Human Capital, Sport Performance, and Salary Determination of Professional Athletes - Roberto Antonietti (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2006)
Thanks to the high availability of data, professional sport represents a unique laboratory in order to test labour market theories and predictions. In particular, one of the most important propositions concerns the role that human capital plays in shaping the life-cycle earnings patterns of workers. To the extent that sport can be considered as a type of human capital investment, human capital theory can help to understand, and empirically assess, how the professional sports labour market rewards performance attributes of players. On this purpose, this piece of work reviews the most important economic contributions focused on the wage determination of professional athletes with the aim of outlining both the emerging common features and the main issues. In so doing, a distinction between professional team-sports and professional single-player sports is done, where the former is represented by the most popular sports in North America and Europe, such as baseball, basketball, hockey and soccer, whereas the latter is primarily represented by professional golf in the US.
Keywords: 330; Profisport; Humankapital; Lohnbildung; USA